2020
DOI: 10.3389/fphy.2019.00240
|View full text |Cite
|
Sign up to set email alerts
|

Jacobi Spectral Galerkin Method for Distributed-Order Fractional Rayleigh–Stokes Problem for a Generalized Second Grade Fluid

Abstract: Distributed-order fractional differential operators provide a powerful tool for mathematical modeling of multiscale multiphysics processes, where the differential orders are distributed over a range of values rather than being just a fixed fraction. In this work, we consider the Rayleigh-Stokes problem for a generalized second-grade fluid which involves the distributed-order fractional derivative in time. We develop a spectral Galerkin method for this model by employing Jacobi polynomials as temporal and spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 45 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…To transform the integral form into the multi-term form (first of the two-step process), two common quadrature rules are often used by researchers: (1) Gauss–Legendre quadrature rule and (2) Newton–Cotes quadrature rule. Based on the Gauss–Legendre quadrature rules [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ], the DO derivative can be approximated using the following multi-term form, where are the weights at the Gauss points chosen for this integration over the DO. Although the Gauss–Legendre quadrature schemes are known to achieve highly accurate results (particularly when dealing with integrands of specific type such as, for example, polynomials), an analysis of the numerical convergence and of the truncation error (including steps 1 and 2) becomes difficult when the integrand consists of fractional derivatives (like , as shown in Equation ( 11 )).…”
Section: Mathematical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To transform the integral form into the multi-term form (first of the two-step process), two common quadrature rules are often used by researchers: (1) Gauss–Legendre quadrature rule and (2) Newton–Cotes quadrature rule. Based on the Gauss–Legendre quadrature rules [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ], the DO derivative can be approximated using the following multi-term form, where are the weights at the Gauss points chosen for this integration over the DO. Although the Gauss–Legendre quadrature schemes are known to achieve highly accurate results (particularly when dealing with integrands of specific type such as, for example, polynomials), an analysis of the numerical convergence and of the truncation error (including steps 1 and 2) becomes difficult when the integrand consists of fractional derivatives (like , as shown in Equation ( 11 )).…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…A few researchers combined the GLSM scheme with an alternating direction implicit (ADI) scheme to improve the accuracy to [ 98 , 139 ]. Numerical studies based on the GJSM approach can be found in [ 85 , 91 , 149 ]. Some interesting conclusions were presented in [ 150 ], which combined a -stage implicit Runge–Kutta method in time and the GJSM/GLSM in space to solve time-space-fractional DODEs.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…The spectral method has become increasingly popular in numerical solutions of partial differential equations due to its high-order accuracy [29][30][31][32][33][34]. For time-dependent partial differential equations, if the spectral scheme is used in spatial, the difference scheme is usually adopted in time.…”
Section: Applications To First-order Hyperbolic Equationsmentioning
confidence: 99%
“…Spectral methods have exponential convergence rates as well as a high accuracy level. The spectral method has been classified into four classes, collocation [14], tau [15], Galerkin [16], and Petrov-Galerkin [17] methods.…”
Section: Introductionmentioning
confidence: 99%